Preparation process of early-warning anti-loosening bolt

By covering the anti-corrosion sheath of polyamide composite material on the outside of the bolt matrix, and using furan-2,5-dione modified graphene oxide and polyamide modified glass fiber, the problem of loosening caused by rust in traditional bolts is solved, and the high corrosion resistance and stability of the bolts are achieved.

CN119773139AActive Publication Date: 2025-04-08CHINATOWER CO LTD HEBEI BRANCH

Patent Information

Application Number
CN202411995197.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Traditional bolts are prone to loosening due to factors such as vibration, mechanical stress, rust and other factors during long-term use, resulting in unstable connections, failure of components, and even serious accidents.

Method used

A layer of anti-corrosion sheath containing polyamide composite material is coated using injection molding process on the outside of the bolt matrix, and graphene oxide is modified with furan-2,5-dione, and combined with polyamide-modified glass fibers, the corrosion resistance of the bolt is improved.

Benefits of technology

It effectively improves the corrosion resistance of bolts, reduces loosening problems caused by rust, and ensures long-term stability and safety of mechanical equipment and structures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation process of an early-warning anti-loosening bolt, and relates to the technical field of bolts, the outer side of a bolt base body is coated with a layer of anti-corrosion sheath containing a polyamide composite material through an injection molding process, so that the effect of improving the corrosion resistance of the bolt is achieved. Furan-2, 5-diketone is used for modifying aminated graphene oxide, maleimide modified graphene oxide is obtained, maleimide has the characteristic of being sensitive to ultraviolet light, and can react with styrene and methyl methacrylate under ultraviolet irradiation, so that vinyl graphene oxide is obtained; and then polyamide modified glass fibers are added, so that the corrosion resistance of the bolt is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bolts, and in particular to a preparation process of early warning anti-loosening bolts. Background Art

[0002] Bolts are one of the most commonly used fasteners in mechanical structures and are widely used in various fields such as automobiles, construction, and aerospace. Early warning anti-loosening bolts combine smart materials that can sense external factors such as stress, temperature, and vibration with traditional bolt fasteners to form a bolt system with self-monitoring capabilities. When the bolts show signs of loosening during use, the material can respond and generate signals or changes, promptly reminding maintenance personnel to conduct inspections and maintenance.

[0003] Therefore, preventing bolts from loosening is an important part of ensuring the safety of mechanical equipment and structures. Traditional bolts will loosen due to vibration, mechanical stress, corrosion and other factors during long-term use, resulting in unstable connections, component failure, and even serious accidents.

[0004] In order to solve the above problems and improve the corrosion resistance of bolts, the present invention provides a preparation process of early warning anti-loosening bolts. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation process of an early warning anti-loosening bolt to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A preparation process of an early warning anti-loosening bolt comprises the following steps:

[0008] Step 1: Take nylon resin and polytetrafluoroethylene powder, stir evenly, add graphene oxide-glass fiber composite, melt extrude and granulate to obtain polyamide composite material;

[0009] Step 2: taking a polyamide composite material, a silane coupling agent, and an antioxidant, and mixing them evenly to obtain an anti-corrosion mixture;

[0010] Step 3: Take Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La, melt, pour, forge, and heat treat to obtain a bolt matrix;

[0011] Step 4: Place the bolt matrix in a mold, add the anti-corrosion mixture into an injection molding machine, perform injection molding, overmolding, take out, and dry to obtain a warning anti-loosening bolt.

[0012] More optimally, the anti-corrosion mixture is composed of the following substances, by weight: 50-60 parts of polyamide composite material, 4-6 parts of silane coupling agent, and 2-3 parts of antioxidant.

[0013] More optimally, the preparation method of the graphene oxide-glass fiber composite is: take maleimide-modified graphene oxide and N,N-dimethylformamide, ultrasonically disperse, add styrene and methyl methacrylate under argon environment, illuminate under ultraviolet lamp for 50-70 minutes, add polyamide modified glass fiber, stir evenly, illuminate under ultraviolet lamp for 50-70 minutes, wash and dry to obtain the graphene oxide-glass fiber composite.

[0014] More optimally, the preparation method of the polyamide modified glass fiber is: take deionized water and emulsifier, stir evenly to obtain a mixed solution; take polyhexamethylene adipamide, thioglycolic acid, and dimethyl sulfoxide, stir evenly, add the mixed solution, stir for 2-3 hours, and obtain a polyhexamethylene adipamide mixed solution; take glass fiber, immerse it in the polyhexamethylene adipamide mixed solution for 20-30 minutes, take it out, and dry it to obtain polyamide modified glass fiber.

[0015] More optimally, the preparation method of the maleimide-modified graphene oxide is: take sodium acetate and deionized water, stir evenly to obtain a sodium acetate solution; take amino-modified graphene oxide, furan-2,5-dione, and chlorobenzene, ultrasonically disperse for 10-15 minutes, heat to 130-135°C under nitrogen, reflux for 2-4 hours, cool to 25-30°C, add sodium acetate solution, heat to 130-135°C under nitrogen, react for 50-70 minutes, cool to 25-30°C, centrifuge, wash, and dry to obtain maleimide-modified graphene oxide.

[0016] More optimally, the preparation method of the amino-modified graphene oxide is: taking graphene oxide, γ-aminopropyltriethoxysilane, and sodium carbonate, centrifuging, precipitating, washing, and drying at 80-85° C. for 46-50 hours to obtain the amino-modified graphene oxide.

[0017] More optimally, the bolt includes the following components, in percentage by mass: 3.0wt%-4.0wt% Mn, 1.5wt%-2.5wt% Ni, 0.4wt%-0.7wt% Si, 0.01wt%-0.04wt% Ge, 0.3wt%-0.4wt% C, 0.01wt%-0.03wt% Ag, 0.008wt%-0.01wt% Bi, 0.001wt%-0.002wt% La, and the balance is Fe and other inevitable impurities.

[0018] More optimally, the antioxidant is any one or more of antioxidant 1010, antioxidant 164, and antioxidant 1076.

[0019] More optimally, the silane coupling agent is KH550.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention coats the outer side of the bolt matrix with a layer of anti-corrosion sheath containing polyamide composite material through injection molding process, thereby achieving the effect of improving the corrosion resistance of the bolt.

[0022] 2. The present invention uses furan-2,5-dione to modify amino graphene oxide to obtain a maleimide-modified graphene oxide. Maleimide is sensitive to ultraviolet light and can react with styrene and methyl methacrylate under ultraviolet light to obtain vinyl graphene oxide. Then, polyamide-modified glass fiber is added, stirred evenly, and illuminated under a 365nm ultraviolet lamp to allow the thiol group on the polyamide-modified glass fiber to react with the vinyl group, so that the vinyl graphene oxide and the polyamide-modified glass fiber are better compounded together, thereby improving the corrosion resistance of the bolt.

[0023] 3. The present invention uses polyamide to modify glass fiber, so that the graphene oxide-glass fiber composite has good dispersion in the polyamide composite matrix, thereby further improving the corrosion resistance of the bolt. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The sources and models of the raw materials involved in the present invention are not specifically limited, and exemplarily include: graphene oxide: model: 796034, which can be purchased from Merck; polyhexamethylene adipamide: model: 132F, which can be purchased from DuPont in the United States; glass fiber: model: S30527, which can be purchased from Shanghai Yuanye Biotechnology Co., Ltd.; nylon resin: model: 1252, which can be purchased from Qingdao Sanli Benno New Materials Co., Ltd.; polytetrafluoroethylene micropowder: model: MP1200, which can be purchased from DuPont in the United States.

[0026] Embodiment 1: A preparation process of a warning anti-loosening bolt, comprising the following steps:

[0027] Step 1: Preparation of polyamide modified glass fiber:

[0028] Take 300 mL of deionized water and 2 g of emulsifier O-20, stir evenly to obtain a mixed solution; take 45 g of polyhexamethylene adipamide, 3 g of thioglycolic acid, and 100 mL of dimethyl sulfoxide, stir evenly, add the mixed solution, stir for 2.5 hours, and obtain a polyhexamethylene adipamide mixed solution; take glass fiber, immerse it in the polyhexamethylene adipamide mixed solution for 25 minutes, take it out, and dry it to obtain a polyamide-modified glass fiber;

[0029] Step 2: Preparation of maleimide-modified graphene oxide:

[0030] Take 0.1 g of graphene oxide, 30 mL of γ-aminopropyltriethoxysilane, and 200 mg of sodium carbonate, centrifuge, precipitate, wash, and dry at 82° C. for 48 h to obtain amino-modified graphene oxide;

[0031] Take 0.2g of sodium acetate and 10mL of deionized water, stir evenly to obtain a sodium acetate solution; take 0.1g of amino-modified graphene oxide, 2g of furan-2,5-dione, and 30mL of chlorobenzene, ultrasonically disperse for 12min, heat to 132°C under nitrogen, reflux for 3h, cool to 28°C, add 10mL of sodium acetate solution, heat to 132°C under nitrogen, react for 60min, cool to 27°C, centrifuge, wash, and dry to obtain maleimide-modified graphene oxide;

[0032] Step 3: Preparation of graphene oxide-glass fiber composite:

[0033] Take 0.1 g of maleimide-modified graphene oxide and 3 mL of N,N-dimethylformamide, ultrasonically disperse, add 0.3 g of styrene and 0.6 g of methyl methacrylate under an argon environment, illuminate for 60 min under a 365 nm ultraviolet lamp, add 3 g of polyamide-modified glass fiber, stir evenly, illuminate for 60 min under a 365 nm ultraviolet lamp, wash and dry to obtain a graphene oxide-glass fiber composite;

[0034] Step 4: Preparation of polyamide composite materials:

[0035] Take 100g of nylon resin and 22g of polytetrafluoroethylene powder, stir evenly, add 20g of graphene oxide-glass fiber composite, melt extrude and granulate to obtain a polyamide composite material;

[0036] Step 5: Preparation of antiseptic mixture:

[0037] Take polyamide composite material, silane coupling agent KH550 and antioxidant, mix them evenly to obtain anti-corrosion mixture;

[0038] Step 6: Preparation of early warning anti-loosening bolts:

[0039] Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La are taken, melted, poured, forged, and heat treated to obtain a bolt matrix;

[0040] The bolt comprises the following components, in percentage by mass: 3.5wt% of Mn, 1.9wt% of Ni, 0.6wt% of Si, 0.03wt% of Ge, 0.35wt% of C, 0.02wt% of Ag, 0.009wt% of Bi, 0.0015wt% of La, and the balance is Fe and other inevitable impurities;

[0041] The bolt matrix is ​​placed in a mold, the anti-corrosion mixture is added to an injection molding machine, injection molding, overmolding, removal, and drying are performed to obtain a warning anti-loosening bolt;

[0042] The anti-corrosion mixture is composed of the following substances, calculated by weight: 55 parts of polyamide composite material, 5 parts of silane coupling agent KH550, and 2.5 parts of antioxidant 1010.

[0043] Embodiment 2: A preparation process of a warning anti-loosening bolt, comprising the following steps:

[0044] Step 1: Preparation of polyamide modified glass fiber:

[0045] Take 300 mL of deionized water and 2 g of emulsifier O-20, stir evenly to obtain a mixed solution; take 45 g of polyhexamethylene adipamide, 3 g of thioglycolic acid, and 100 mL of dimethyl sulfoxide, stir evenly, add the mixed solution, stir for 2 h, and obtain a polyhexamethylene adipamide mixed solution; take glass fiber, immerse it in the polyhexamethylene adipamide mixed solution for 20 min, take it out, and dry it to obtain a polyamide-modified glass fiber;

[0046] Step 2: Preparation of maleimide-modified graphene oxide:

[0047] Take 0.1 g of graphene oxide, 30 mL of γ-aminopropyltriethoxysilane, and 200 mg of sodium carbonate, centrifuge, precipitate, wash, and dry at 80° C. for 46 h to obtain amino-modified graphene oxide;

[0048] Take 0.2g of sodium acetate and 10mL of deionized water, stir evenly to obtain a sodium acetate solution; take 0.1g of amino-modified graphene oxide, 2g of furan-2,5-dione, and 30mL of chlorobenzene, ultrasonically disperse for 10min, heat to 130°C under nitrogen, reflux for 2h, cool to 25°C, add 10mL of sodium acetate solution, heat to 130°C under nitrogen, react for 50min, cool to 25°C, centrifuge, wash, and dry to obtain maleimide-modified graphene oxide;

[0049] Step 3: Preparation of graphene oxide-glass fiber composite:

[0050] Take 0.1 g of maleimide-modified graphene oxide and 3 mL of N,N-dimethylformamide, disperse by ultrasonication, add 0.3 g of styrene and 0.6 g of methyl methacrylate under an argon environment, irradiate under a 365 nm ultraviolet lamp for 50 min, add 3 g of polyamide-modified glass fiber, stir evenly, irradiate under a 365 nm ultraviolet lamp for 50 min, wash and dry to obtain a graphene oxide-glass fiber composite;

[0051] Step 4: Preparation of polyamide composite materials:

[0052] Take 100g of nylon resin and 22g of polytetrafluoroethylene powder, stir evenly, add 20g of graphene oxide-glass fiber composite, melt extrude and granulate to obtain a polyamide composite material;

[0053] Step 5: Preparation of antiseptic mixture:

[0054] Take polyamide composite material, silane coupling agent KH550 and antioxidant, mix them evenly to obtain anti-corrosion mixture;

[0055] Step 6: Preparation of early warning anti-loosening bolts:

[0056] Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La are taken, melted, poured, forged, and heat treated to obtain a bolt matrix;

[0057] The bolt comprises the following components, in percentage by mass: 3.0wt% Mn, 1.5wt% Ni, 0.4wt% Si, 0.01wt% Ge, 0.3wt% C, 0.01wt% Ag, 0.008wt% Bi, 0.001wt% La, and the balance is Fe and other inevitable impurities;

[0058] The bolt matrix is ​​placed in a mold, the anti-corrosion mixture is added to an injection molding machine, injection molding, overmolding, removal, and drying are performed to obtain a warning anti-loosening bolt;

[0059] The anti-corrosion mixture is composed of the following substances, calculated by weight: 50 parts of polyamide composite material, 4 parts of silane coupling agent KH550, and 2 parts of antioxidant 164.

[0060] Embodiment 3: A preparation process of a warning anti-loosening bolt, comprising the following steps:

[0061] Step 1: Preparation of polyamide modified glass fiber:

[0062] Take 300 mL of deionized water and 2 g of emulsifier O-20, stir evenly to obtain a mixed solution; take 45 g of polyhexamethylene adipamide, 3 g of thioglycolic acid, and 100 mL of dimethyl sulfoxide, stir evenly, add the mixed solution, stir for 3 hours, and obtain a polyhexamethylene adipamide mixed solution; take glass fiber, immerse it in the polyhexamethylene adipamide mixed solution for 30 minutes, take it out, and dry it to obtain a polyamide-modified glass fiber;

[0063] Step 2: Preparation of maleimide-modified graphene oxide:

[0064] Take 0.1 g of graphene oxide, 30 mL of γ-aminopropyltriethoxysilane, and 200 mg of sodium carbonate, centrifuge, precipitate, wash, and dry at 85° C. for 50 h to obtain amino-modified graphene oxide;

[0065] Take 0.2g of sodium acetate and 10mL of deionized water, stir evenly to obtain a sodium acetate solution; take 0.1g of amino-modified graphene oxide, 2g of furan-2,5-dione, and 30mL of chlorobenzene, ultrasonically disperse for 15min, heat to 135°C under nitrogen, reflux for 4h, cool to 30°C, add 10mL of sodium acetate solution, heat to 135°C under nitrogen, react for 70min, cool to 30°C, centrifuge, wash, and dry to obtain maleimide-modified graphene oxide;

[0066] Step 3: Preparation of graphene oxide-glass fiber composite:

[0067] Take 0.1 g of maleimide-modified graphene oxide and 3 mL of N,N-dimethylformamide, disperse by ultrasonication, add 0.3 g of styrene and 0.6 g of methyl methacrylate under an argon environment, irradiate under a 365 nm ultraviolet lamp for 70 min, add 3 g of polyamide-modified glass fiber, stir evenly, irradiate under a 365 nm ultraviolet lamp for 70 min, wash and dry to obtain a graphene oxide-glass fiber composite;

[0068] Step 4: Preparation of polyamide composite materials:

[0069] Take 100g of nylon resin and 22g of polytetrafluoroethylene powder, stir evenly, add 20g of graphene oxide-glass fiber composite, melt extrude and granulate to obtain a polyamide composite material;

[0070] Step 5: Preparation of antiseptic mixture:

[0071] Take polyamide composite material, silane coupling agent KH550 and antioxidant, mix them evenly to obtain anti-corrosion mixture;

[0072] Step 6: Preparation of early warning anti-loosening bolts:

[0073] Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La are taken, melted, poured, forged, and heat treated to obtain a bolt matrix;

[0074] The bolt comprises the following components, in percentage by mass: 4.0wt% of Mn, 2.5wt% of Ni, 0.7wt% of Si, 0.04wt% of Ge, 0.4wt% of C, 0.03wt% of Ag, 0.01wt% of Bi, 0.002wt% of La, and the balance is Fe and other inevitable impurities;

[0075] The bolt matrix is ​​placed in a mold, the anti-corrosion mixture is added to an injection molding machine, injection molding, overmolding, removal, and drying are performed to obtain a warning anti-loosening bolt;

[0076] The anti-corrosion mixture is composed of the following substances, calculated by weight: 60 parts of polyamide composite material, 6 parts of silane coupling agent KH550, and 3 parts of antioxidant 1076.

[0077] Comparative Example 1: No thioglycolic acid is added to the polyamide modified glass fiber, and the rest is the same as Example 1:

[0078] Step 1: Preparation of polyamide modified glass fiber:

[0079] Take 300 mL of deionized water and 2 g of emulsifier O-20, stir evenly to obtain a mixed solution; take 45 g of polyhexamethylene adipamide and 100 mL of dimethyl sulfoxide, stir evenly, add the mixed solution, stir for 2.5 hours to obtain a polyhexamethylene adipamide mixed solution; take glass fiber, immerse it in the polyhexamethylene adipamide mixed solution for 25 minutes, take it out, and dry it to obtain a polyamide-modified glass fiber;

[0080] Step 2: Preparation of maleimide-modified graphene oxide:

[0081] Take 0.1 g of graphene oxide, 30 mL of γ-aminopropyltriethoxysilane, and 200 mg of sodium carbonate, centrifuge, precipitate, wash, and dry at 82° C. for 48 h to obtain amino-modified graphene oxide;

[0082] Take 0.2g of sodium acetate and 10mL of deionized water, stir evenly to obtain a sodium acetate solution; take 0.1g of amino-modified graphene oxide, 2g of furan-2,5-dione, and 30mL of chlorobenzene, ultrasonically disperse for 12min, heat to 132°C under nitrogen, reflux for 3h, cool to 28°C, add 10mL of sodium acetate solution, heat to 132°C under nitrogen, react for 60min, cool to 27°C, centrifuge, wash, and dry to obtain maleimide-modified graphene oxide;

[0083] Step 3: Preparation of graphene oxide-glass fiber composite:

[0084] Take 0.1 g of maleimide-modified graphene oxide and 3 mL of N,N-dimethylformamide, ultrasonically disperse, add 0.3 g of styrene and 0.6 g of methyl methacrylate under an argon environment, illuminate for 60 min under a 365 nm ultraviolet lamp, add 3 g of polyamide-modified glass fiber, stir evenly, illuminate for 60 min under a 365 nm ultraviolet lamp, wash and dry to obtain a graphene oxide-glass fiber composite;

[0085] Step 4: Preparation of polyamide composite materials:

[0086] Take 100g of nylon resin and 22g of polytetrafluoroethylene powder, stir evenly, add 20g of graphene oxide-glass fiber composite, melt extrude and granulate to obtain a polyamide composite material;

[0087] Step 5: Preparation of antiseptic mixture:

[0088] Take polyamide composite material, silane coupling agent KH550 and antioxidant, mix them evenly to obtain anti-corrosion mixture;

[0089] Step 6: Preparation of early warning anti-loosening bolts:

[0090] Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La are taken, melted, poured, forged, and heat treated to obtain a bolt matrix;

[0091] The bolt comprises the following components, in percentage by mass: 3.5wt% of Mn, 1.9wt% of Ni, 0.6wt% of Si, 0.03wt% of Ge, 0.35wt% of C, 0.02wt% of Ag, 0.009wt% of Bi, 0.0015wt% of La, and the balance is Fe and other inevitable impurities;

[0092] The bolt matrix is ​​placed in a mold, the anti-corrosion mixture is added to an injection molding machine, injection molding, overmolding, removal, and drying are performed to obtain a warning anti-loosening bolt;

[0093] The anti-corrosion mixture is composed of the following substances, calculated by weight: 55 parts of polyamide composite material, 5 parts of silane coupling agent KH550, and 2.5 parts of antioxidant 1010.

[0094] Comparative Example 2: No glass fiber is added, and the rest is the same as Example 1:

[0095] Step 1: Preparation of maleimide-modified graphene oxide:

[0096] Take 0.1 g of graphene oxide, 30 mL of γ-aminopropyltriethoxysilane, and 200 mg of sodium carbonate, centrifuge, precipitate, wash, and dry at 82° C. for 48 h to obtain amino-modified graphene oxide;

[0097] Take 0.2g of sodium acetate and 10mL of deionized water, stir evenly to obtain a sodium acetate solution; take 0.1g of amino-modified graphene oxide, 2g of furan-2,5-dione, and 30mL of chlorobenzene, ultrasonically disperse for 12min, heat to 132°C under nitrogen, reflux for 3h, cool to 28°C, add 10mL of sodium acetate solution, heat to 132°C under nitrogen, react for 60min, cool to 27°C, centrifuge, wash, and dry to obtain maleimide-modified graphene oxide;

[0098] Step 2: Preparation of vinyl graphene oxide:

[0099] Take 0.1 g of maleimide-modified graphene oxide and 3 mL of N,N-dimethylformamide, disperse by ultrasonication, add 0.3 g of styrene and 0.6 g of methyl methacrylate under an argon environment, irradiate under a 365 nm ultraviolet lamp for 60 min, wash and dry to obtain vinyl graphene oxide;

[0100] Step 3: Preparation of polyamide composite materials:

[0101] Take 100g of nylon resin and 22g of polytetrafluoroethylene powder, stir evenly, add 20g of vinyl graphene oxide, melt extrude and granulate to obtain a polyamide composite material;

[0102] Step 4: Preparation of antiseptic mixture:

[0103] Take polyamide composite material, silane coupling agent KH550 and antioxidant, mix them evenly to obtain anti-corrosion mixture;

[0104] Step 5: Preparation of early warning anti-loosening bolts:

[0105] Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La are taken, melted, poured, forged, and heat treated to obtain a bolt matrix;

[0106] The bolt comprises the following components, in percentage by mass: 3.5wt% of Mn, 1.9wt% of Ni, 0.6wt% of Si, 0.03wt% of Ge, 0.35wt% of C, 0.02wt% of Ag, 0.009wt% of Bi, 0.0015wt% of La, and the balance is Fe and other inevitable impurities;

[0107] The bolt matrix is ​​placed in a mold, the anti-corrosion mixture is added to an injection molding machine, injection molding, overmolding, removal, and drying are performed to obtain a warning anti-loosening bolt;

[0108] The anti-corrosion mixture is composed of the following substances, calculated by weight: 55 parts of polyamide composite material, 5 parts of silane coupling agent KH550, and 2.5 parts of antioxidant 1010.

[0109] Comparative Example 3: The glass fiber is not modified by using polyamide, and the rest is the same as Example 1:

[0110] Step 1: Preparation of modified glass fiber:

[0111] Take 3g of thioglycolic acid and 100mL of dimethyl sulfoxide, stir evenly to obtain a thioglycolic acid solution; take glass fiber, immerse it in the thioglycolic acid solution for 25 minutes, take it out and dry it to obtain a modified glass fiber;

[0112] Step 2: Preparation of maleimide-modified graphene oxide:

[0113] Take 0.1 g of graphene oxide, 30 mL of γ-aminopropyltriethoxysilane, and 200 mg of sodium carbonate, centrifuge, precipitate, wash, and dry at 82° C. for 48 h to obtain amino-modified graphene oxide;

[0114] Take 0.2g of sodium acetate and 10mL of deionized water, stir evenly to obtain a sodium acetate solution; take 0.1g of amino-modified graphene oxide, 2g of furan-2,5-dione, and 30mL of chlorobenzene, ultrasonically disperse for 12min, heat to 132°C under nitrogen, reflux for 3h, cool to 28°C, add 10mL of sodium acetate solution, heat to 132°C under nitrogen, react for 60min, cool to 27°C, centrifuge, wash, and dry to obtain maleimide-modified graphene oxide;

[0115] Step 3: Preparation of graphene oxide-glass fiber composite:

[0116] Take 0.1 g of maleimide-modified graphene oxide and 3 mL of N,N-dimethylformamide, disperse by ultrasonication, add 0.3 g of styrene and 0.6 g of methyl methacrylate under an argon environment, irradiate under a 365 nm ultraviolet lamp for 60 min, add 3 g of modified glass fiber, stir evenly, irradiate under a 365 nm ultraviolet lamp for 60 min, wash and dry to obtain a graphene oxide-glass fiber composite;

[0117] Step 4: Preparation of polyamide composite materials:

[0118] Take 100g of nylon resin and 22g of polytetrafluoroethylene powder, stir evenly, add 20g of graphene oxide-glass fiber composite, melt extrude and granulate to obtain a polyamide composite material;

[0119] Step 5: Preparation of antiseptic mixture:

[0120] Take polyamide composite material, silane coupling agent KH550 and antioxidant, mix them evenly to obtain anti-corrosion mixture;

[0121] Step 6: Preparation of early warning anti-loosening bolts:

[0122] Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La are taken, melted, poured, forged, and heat treated to obtain a bolt matrix;

[0123] The bolt comprises the following components, in percentage by mass: 3.5wt% of Mn, 1.9wt% of Ni, 0.6wt% of Si, 0.03wt% of Ge, 0.35wt% of C, 0.02wt% of Ag, 0.009wt% of Bi, 0.0015wt% of La, and the balance is Fe and other inevitable impurities;

[0124] The bolt matrix is ​​placed in a mold, the anti-corrosion mixture is added to an injection molding machine, injection molding, overmolding, removal, and drying are performed to obtain a warning anti-loosening bolt;

[0125] The anti-corrosion mixture is composed of the following substances, calculated by weight: 55 parts of polyamide composite material, 5 parts of silane coupling agent KH550, and 2.5 parts of antioxidant 1010.

[0126] experiment:

[0127] The early warning anti-loosening bolts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests, and the tensile strength of the early warning anti-loosening bolts was tested with reference to GB / T 228-2010 and GB / T 3098.1-2010; the early warning anti-loosening bolts were immersed in a 15% by mass hydrochloric acid aqueous solution for 1 hour, taken out, and the corrosion loss of the early warning anti-loosening bolts before and after the immersion was tested, and the data obtained are as follows:

[0128] Tensile strength / Mpa Corrosion loss / % Example 1 1521 0.004 Example 2 1517 0.005 Example 3 1523 0.004 Comparative Example 1 1511 0.073 Comparative Example 2 1493 0.162 Comparative Example 3 1506 0.090

[0129] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, thioglycolic acid is not added to the polyamide modified glass fiber, the composite effect of vinyl graphene oxide and polyamide modified glass fiber is not good, and the corrosion resistance of the bolt is reduced. In Comparative Example 2, glass fiber is not added, and the corrosion resistance of the early warning anti-loosening bolt is greatly reduced. In Comparative Example 3, polyamide is not used to modify the glass fiber, and the dispersion of the graphene oxide-glass fiber composite in the polyamide composite matrix is ​​not good, the corrosion resistance of the bolt is reduced, and the corrosion loss is increased. In Examples 1 to 3 of the present invention, furan-2,5-dione is used to modify amino graphene oxide to obtain a maleimide-modified graphene oxide. Maleimide is sensitive to ultraviolet light and can react with styrene and methyl methacrylate under ultraviolet light to obtain vinyl graphene oxide. Then, polyamide-modified glass fiber is added, stirred evenly, and illuminated under a 365nm ultraviolet lamp to react the thiol group on the polyamide-modified glass fiber with the vinyl group, so that the vinyl graphene oxide and the polyamide-modified glass fiber are better compounded together, thereby improving the corrosion resistance of the bolt.

[0130] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A preparation process for an early warning anti-loosening bolt, characterized in that: The following steps are involved: Step 1: Take nylon resin and polytetrafluoroethylene powder, stir evenly, add graphene oxide-glass fiber composite, melt extrude and granulate to obtain polyamide composite material; Step 2: taking a polyamide composite material, a silane coupling agent, and an antioxidant, and mixing them evenly to obtain an anti-corrosion mixture; Step 3: Take Fe, Mn, Ni, Si, Ge, C, Ag, Bi, and La, melt, pour, forge, and heat treat to obtain a bolt matrix; Step 4: Place the bolt matrix in a mold, add the anti-corrosion mixture into an injection molding machine, perform injection molding, overmolding, take out, and dry to obtain a warning anti-loosening bolt.

2. The preparation process of the early warning anti-loosening bolt according to claim 1 is characterized in that: The anti-corrosion mixture is composed of the following substances, calculated by weight: 50-60 parts of polyamide composite material, 4-6 parts of silane coupling agent, and 2-3 parts of antioxidant.

3. The preparation process of the early warning anti-loosening bolt according to claim 1 is characterized in that: The preparation method of the graphene oxide-glass fiber composite is as follows: maleimide-modified graphene oxide and N,N-dimethylformamide are taken, ultrasonically dispersed, styrene and methyl methacrylate are added under an argon environment, and the mixture is illuminated under an ultraviolet lamp for 50-70 minutes, polyamide-modified glass fiber is added, stirred evenly, and the mixture is illuminated under an ultraviolet lamp for 50-70 minutes, washed, and dried to obtain the graphene oxide-glass fiber composite.

4. The preparation process of the early warning anti-loosening bolt according to claim 3 is characterized in that: The preparation method of the polyamide modified glass fiber is as follows: take deionized water and an emulsifier, stir evenly to obtain a mixed solution; take polyhexamethylene adipamide, thioglycolic acid, and dimethyl sulfoxide, stir evenly, add the mixed solution, stir for 2-3 hours, and obtain a polyhexamethylene adipamide mixed solution; take glass fiber, immerse it in the polyhexamethylene adipamide mixed solution for 20-30 minutes, take it out, and dry it to obtain the polyamide modified glass fiber.

5. The preparation process of the early warning anti-loosening bolt according to claim 3 is characterized in that: The preparation method of the maleimide-modified graphene oxide is as follows: sodium acetate and deionized water are taken and stirred evenly to obtain a sodium acetate solution; amination-modified graphene oxide, furan-2,5-dione and chlorobenzene are taken and ultrasonically dispersed for 10-15 minutes, heated to 130-135° C. under nitrogen, refluxed for 2-4 hours, cooled to 25-30° C., added with sodium acetate solution, heated to 130-135° C. under nitrogen, reacted for 50-70 minutes, cooled to 25-30° C., centrifuged, washed and dried to obtain maleimide-modified graphene oxide.

6. The process for preparing the early warning anti-loosening bolt according to claim 5, characterized in that: The preparation method of the aminated graphene oxide is as follows: taking graphene oxide, γ-aminopropyltriethoxysilane and sodium carbonate, centrifuging, precipitating, washing and drying at 80-85° C. for 46-50 hours to obtain the aminated graphene oxide.

7. The preparation process of the early warning anti-loosening bolt according to claim 1 is characterized in that: The bolt includes the following components, calculated by mass percentage: 3.0wt%-4.0wt% of Mn, 1.5wt%-2.5wt% of Ni, 0.4wt%-0.7wt% of Si, 0.01wt%-0.04wt% of Ge, 0.3wt%-0.4wt% of C, 0.01wt%-0.03wt% of Ag, 0.008wt%-0.01wt% of Bi, 0.001wt%-0.002wt% of La, and the balance is Fe and other inevitable impurities.

8. The preparation process of the early warning anti-loosening bolt according to claim 1, characterized in that: The antioxidant is any one or more of antioxidant 1010 , antioxidant 164 , and antioxidant 1076 .

9. The preparation process of the early warning anti-loosening bolt according to claim 1, characterized in that: The silane coupling agent is KH550.

10. An early warning anti-loosening bolt prepared according to the preparation process of an early warning anti-loosening bolt according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polytetrafluoroethylene modified abrasive-resistance glass fiber reinforced PA66 electric power fitting material and preparation method thereof

    CN106543713A

  • Preparation method of super-wear-resistant, flame-retardant, high-strength and mould-resistant graphene composite material

    CN112457548A

  • High-temperature-resistant and corrosion-resistant glass fiber electronic cloth and preparation method thereof

    CN112501916A

  • High-strength corrosion-resistant bolt material and preparation method thereof

    CN114875307A

  • High-temperature-resistant and corrosion-resistant glass fiber electronic cloth

    CN115821574A

Cited By

  • Anti-loosening bolt and preparation process thereof

    CN121157280A

  • Anti-loose bolt and manufacturing process thereof

    CN121157280B